Protective Effect of Mirtazapine on Brain Tissue in Bleomycin-induced Neurotoxicity in Rats Model - Aldossary, Sara A. (Asian Journal of Pharmaceutics (AJP), 2025)
Neurotoxicity refers to the detrimental impact of chemical or biological agents on the structure and function of the nervous system. It can result from various interrelated mechanisms, including oxidative stress, neuroinflammation, mitochondrial dysfunction, and neuronal apoptosis. Bleomycin (BLM), a commonly used chemotherapeutic agent, has been associated with neurotoxic effects, potentially mediated by oxidative damage and mitochondrial impairment. However, the neuroprotective potential of mirtazapine against BLM-induced neurotoxicity in central nervous system tissues remains inadequately explored. Aim: This study aimed to investigate the protective effects of mirtazapine on brain tissue in a rat model of BLM-induced neurotoxicity, with a particular focus on histopathological alterations. Methods: Thirty-five adult male Wistar rats were randomly assigned to five groups: Control, BLM, BLM plus mirtazapine (15 or 30 mg/kg), and mirtazapine-only groups. Neurotoxicity was induced through a single intratracheal dose of BLM (5 mg/kg), followed by daily oral administration of mirtazapine for 14 days. On day 15, animals were euthanized, and brain tissues were harvested for histological examination. Results: Histological assessment revealed that BLM caused significant neuronal degeneration in the cerebral cortex and hippocampus. Mirtazapine at 15 mg/kg provided moderate neuroprotection, while the 30 mg/kg dose markedly preserved cortical and hippocampal architecture, indicating substantial histological improvement. Conclusion: Mirtazapine exhibited a dose-dependent neuroprotective effect against BLM-induced brain toxicity, likely through the preservation of neuronal integrity. These findings highlight its potential as a therapeutic candidate for mitigating chemotherapy-related neurotoxicity.